1998
DOI: 10.1523/jneurosci.18-13-05035.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pedunculopontine Tegmental Nucleus Lesions on Responding for Intravenous Heroin under Different Schedules of Reinforcement

Abstract: The pedunculopontine tegmental nucleus (PPTg) is believed to play important roles in reward and learning. We examined the effect of PPTg lesions (0.5 microl of 0.1 M NMDA injected bilaterally over 10 min) on the learning of an operant response for opiate reward. In 14 adult male Long-Evans rats, bilateral lesions of the PPTg disrupted the acquisition of responding for intravenous heroin (0.1 mg/kg infused at a rate of 0.25 ml/28 sec) on a fixed ratio-1 (FR-1) schedule of reinforcement. The 12 remaining lesione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 57 publications
4
79
1
Order By: Relevance
“…This suggests that the PVT may be important as a generalized arousal relay to mesolimbic DA terminal fields, including the NAS, PFC, and AMG. In addition, in view of recent data suggesting that pontine cholinergic reticular formation neurons are involved in the rewarding effects of opiates (Olmstead et al, 1998), and because these neurons are a primary source of afferents to the PV T, the PVT may subserve the rewarding properties of psychostimulants and other drugs of abuse.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…This suggests that the PVT may be important as a generalized arousal relay to mesolimbic DA terminal fields, including the NAS, PFC, and AMG. In addition, in view of recent data suggesting that pontine cholinergic reticular formation neurons are involved in the rewarding effects of opiates (Olmstead et al, 1998), and because these neurons are a primary source of afferents to the PV T, the PVT may subserve the rewarding properties of psychostimulants and other drugs of abuse.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…The pedunculopontine tegmental nucleus (PPTg) is involved in a variety of rewarded behaviors including the self-administration of drugs (Bechara and van der Kooy 1989;Yeomans et al 1993Yeomans et al , 2000Franklin 1994, 1997;Olmstead et al 1998;Corrigall et al 1999). For nicotine, part of the circuitry involved in self-administration includes the population of cholinergic neurons in the PPTg that projects to the ventral tegmental area and substantia nigra, and terminates monosynaptically on midbrain dopamine neurons (Bolam et al 1991;Oakman et al 1995); neurotoxin-produced lesion of these cholinergic neurons attenuates nicotine self-administration (Lança et al 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…PPTg activation increases dopamine neurons firing (Klitenick and Kalivas 1994;Floresco et al 2003), and it has been suggested that this nucleus controls goal-directed behavior by integrating sensory and limbic inputs to modulate the motivational, rewarding, and noveltydetection functions of the VTA (Olmstead et al 1998). Indeed, it was proposed that PPTg neurons could relay the excitatory components of both expected and actual reward signals to VTA dopamine neurons (Laviolette et al 2002;Pidoplichko et al 2004;Kobayashi and Okada 2007;Okada et al 2009).…”
mentioning
confidence: 99%